Usefulness of the “newly designed” short-type single-balloon enteroscope for ERCP in patients with Roux-en-Y gastrectomy: a pilot study - Tanisaka, Yuki; Ryozawa, Shomei; Mizuide, Masafumi; Kobayashi, Masanori; Fujita, Akashi; Minami, Kazuhiro; Kobatake, Tsutomu; Omiya, Kumiko; Iwano, Hirotoshi; Araki, Ryuichiro (Endoscopy International Open, 2018)
Background and aims In recent years, the short single-balloon enteroscope (SBE) has been used during endoscopic retrograde cholangiopancreatography (ERCP) for patients with surgically altered anatomy and has been reported to be useful. However, difficulties remain, and the procedures and devices need improvements. We assessed the usefulness and superiority of a new short SBE equipped with passive bending and high-force transmission by comparisons with outcomes using the conventional short SBE.Methods This study evaluated short SBE-assisted ERCP-related procedures for Roux-en-Y gastrectomy between September 2011 and October 2017. Outcomes including the procedural success rate, which was the primary outcome, were assessed to compare the conventional short SBE (SIF-Y0004 [prototype]) and the new short SBE (SIF-H290S).Results Of 74 procedures performed in 61 patients, 51 procedures in 39 patients involved the SIF-Y0004, and 23 procedures in 22 patients involved the SIF-H290S. The procedural success rates were 70.6 % for SIF-Y0004, and 95.7 % for SIF-H290S, representing better results for the new short SBE (P = 0.02). The new short SBE also had a superior diagnostic success rate (P = 0.047) and median time to reach the blind end (P < 0.001).Conclusions Roux-en-Y gastrectomy patients treated with the new short SBE had better outcomes than those treated with conventional short SBE. More cases need to be studied; however, the new short SBE has the potential to improve ERCP outcomes in patients with surgically altered anatomy.